Robust image watermarking based on schur decomposition - Toha, Ahmad; Ernawan, Ferda; Amrullah, Agit (College of Education, Al-Iraqia University, 2024)
The advanced of internet technology allows unauthorized people to distribute multimedia data. Copyright protection for digital images is needed to protect the intellectual properties of the digital image. This study presents a colour image watermarking using schur decomposition for protecting the digital copyright. This study investigates the significant contribution of the orthogonal U of schur decomposition with the size of 8´8 pixels. The proposed scheme embeds a watermark on the (U2, U6) of the U matrix to achieve high invisibly and robustness of the embedded watermark. The relationship of each coefficient on the U matrix of Schur decomposition is also investigated. The experimental results demonstrate that the proposed scheme achieved high invisibility with the SSIM value of about 0.9951. The proposed scheme was also evaluated by several image processing attacks such as added noise, resized image, filtered image, and compressed image. The proposed scheme obtained a high level of resilience with the NC value of 0.996.